A mathematical analysis of the bioenergetics of hurdling - Ward-Smith, A. J. (Journal of Sports Sciences, 1997)
A mathematical model of the bioenergetics of running has been extended to apply to hurdling. This has been achieved by two principal modifications. First, a new term has been added to the energy equation to account for the potential energy required to negotiate each hurdle. Secondly, the term describing the degradation of mechanical energy to thermal energy has been modified to account for the adjustments in stride pattern necessary to negotiate the hurdles. A comparison of predicted and actual running times of elite athletes was made and good levels of agreement were achieved.